PREDICTING NURSING LEADERSHIP ROLES OF PATIENT SAFETY IN THE OPERATING ROOM. - Sofia de Carvalho Mota, Ana; Filomena de Oliveira Mendes Castilho, Amélia; Ferreira Pereira Martins, Maria Manuela (Revista Baiana de Enfermagem, 2022)
Objective: to identify the leadership perceived by perioperative nurses and to determine the role of leadership predictors of patient safety in the operating room. Method: descriptive and explanatory study in a sample of 1,001 nurses, using the patient safety questionnaire in the operating room and Quinn’s leadership instrument adapted to health. The IBM SPSS Statistics application, version 25.0, was used in the data processing. Result: all leadership dimensions were higher than the midpoint of the scale (M>4). A minimum value was observed in the role of Innovator (M=4.63) and maximum in the Producer (M=5.04). The regression models allowed pointing out that leadership roles are predictors of patient safety in the operating room, especially the roles Monitor, Producer and Facilitator. Conclusion: perioperative nurses have moderately positive perception of leadership exercise, indicating the need to promote the development of different leadership roles exercised by perioperative management nurses.